2016
DOI: 10.1161/jaha.115.002508
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 Signaling Is Required for Anterior Second Heart Field Cellular Organization and Cardiac Outflow Tract Development

Abstract: BackgroundThe small GTPase Rac1 regulates diverse cellular functions, including both apicobasal and planar cell polarity pathways; however, its role in cardiac outflow tract (OFT) development remains unknown. In the present study, we aimed to examine the role of Rac1 in the anterior second heart field (SHF) splanchnic mesoderm and subsequent OFT development during heart morphogenesis.Methods and ResultsUsing the Cre/loxP system, mice with an anterior SHF‐specific deletion of Rac1 (Rac1 SHF) were generated. Emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 55 publications
(128 reference statements)
1
18
0
Order By: Relevance
“…We have recently shown that defects in SHF signaling results in thin myocardium, septal defects and OFT defects [23,33]. The defective SHF progenitor contribution may explain the majority of heart malformations in the OFT, cardiac septum and cardiac valves induced by pregestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that defects in SHF signaling results in thin myocardium, septal defects and OFT defects [23,33]. The defective SHF progenitor contribution may explain the majority of heart malformations in the OFT, cardiac septum and cardiac valves induced by pregestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In our study population, 11.9% of patients had a history of myocardial infarction; we found that 53.6% of patients with old myocardial infarction were not taking the AAβ, which suggests that application of medicine for improving prognosis of myocardial infarction was still inadequate. A recent clinical research conducted by Liu et al [ 16 ] that focused on the use and trends of ACEI/ARB therapy in China over the past decade (2001–2011), after analyzing 102,003 patients, they found that one-third of Chinese AMI patients with Class I indications do not receive ACEI/ARB therapy during hospitalization, with little improvement in rates over time. The underutilization of ACEI/ARB therapy was also observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The SHF was initially described as a progenitor field for the cardiac OFT and a rich literature has established the requirement of anterior SHF contributions for OFT development [5, 10-19, 60-63]. More recently, the contribution of posterior SHF cardiac progenitors to the OFT and the future subpulmonary myocardium has been reported, however, the mechanistic requirement for this contribution is not well understood [45, 64-66].…”
Section: Discussionmentioning
confidence: 99%